(untitled) (CAHIERS MAGELLANES-NS, 2024)
The global push for digitization leading to a significant expansion of digital platforms across various sectors has introduced new complexities and challenges pertaining to competition regulation in digital markets. There is an increasing need for specialized competition law to promote competition, foster innovation, and safeguard consumer interests in the digital domain. Regulators around the world are currently working on formulating an effective framework to address competition in the digital sphere. There is a growing consensus that traditional methods of ex-post evaluation may not be suitable for assessing the performance of major digital platforms. A significant development in this area is exemplified by the introduction of the Digital Markets Act 2022 by the European Union, which aimed to promote a nascent regime of ex-ante antitrust regulations. Similarly, recognizing the limitations of the existing ex-post framework within the Competition Act, 2002 in addressing concerns pertaining to alleged anti-competitive behaviour of large digital corporations, the Indian authorities have also put forth a proposal for new legislation. It has been recommended by the expert committees to establish a framework for designating certain digital market participants as Systematically Significant Digital Intermediaries (SIDIs), thereby subjecting them to specific regulatory measures under the new law. The proposed bill aims to establish proactive measures to enhance the existing competition regulatory framework by delineating prominent digital corporations with a substantial footprint in India within specific digital sectors, and establishing predetermined guidelines for their operations. This legislation seeks to enforce certain standards on larger corporations depending on their revenue, total merchandise value, user volume, and additional criteria.